FPGA-Jetson based hardware real-time co-simulation for smart grid - Tong DUAN; Venkata Dinavahi; Tianshi CHENG (物联网学报)
Smart grid is a power-communication coupled cyber-physical power system (CPPS), where the two-domain coupling features make the real-time simulation difficult.Different from the existing software-based co-simulation methods, a FPGA-Jetson based real-time co-simulation platform for smart grid by leveraging the FPGA’'s programmable computation capability and Jetson’s real-time operating system was designed.The power system simulation was carried out on the FPGA board, the information communication system simulation was completed on Jetson platform, and the two-domain information interaction was simulated through the PCIe channel.By making full use of the computing and data transmission capabilities of each module, the real-time simulation of the combination of power grid and communication network was realized.Finally, the corresponding specific modeling and parameters were designed for the two representative smart grid scenarios: hybrid AC-DC transmission network and micro-grid, the validity and scalability of the proposed real-time co-simulation architecture were verified.